Growth Arrest Specific Gene 6 Protein Concentration in Cerebrospinal Fluid Correlates with Relapse Severity in Multiple Sclerosis - P. P. Sainaghi; L. Collimedaglia; F. Alciato; R. Molinari; D. Sola; E. Ranza; P. Naldi; F. Monaco; M. Leone; M. Pirisi; G. C. Avanzi (Mediators of Inflammation)
Background. Growth arrest specific gene 6 (Gas6) protein enhances survival of oligodendrocytes and neurons, and it is involved in autoimmunity. Therefore, we aimed to verify whether cerebrospinal-fluid (CSF) Gas6 concentration may represent a biomarker of disease activity in multiple sclerosis. Methods. Sixty-five patients who underwent a spinal tap during relapse of relapsing/remitting multiple sclerosis (RR-MS)(McDonald-criteria) were studied. Forty patients affected by noninflammatory/nonautoimmune neurological diseases served as controls. Relapse was defined according to Schumacher criteria. Symptoms were grouped according to Kurtzke-Functional System (FS). Clinical characteristics of the relapse, duration, Expanded-Disability-Status Scale (EDSS) change, number of FS involved, completeness of recovery, age, steroid therapy, were categorised. Patients were followed at 6-month intervals to assess relapse rate and EDSS progression. Gas6 was measured (CSF, plasma) by in-house-enzyme-linked immunoassay (ELISA). Results. Higher CSF Gas6 concentrations were observed in relapses lasting ≤60 days (8.7 ± 3.9 ng/mL) versus >60 days (6.5 ± 2.6) or controls (6.5 ± 2.4; P=0.05), with ≤2 FS involved (8.5 ± 3.8) versus >2 FS (5.6 ± 2.5) (P<0.05) and EDSS change ≤2.5 points (8.8 ± 3.7) versus >2.5 (6.5 ± 3.5) (P=0.04). Conversely, CSF Gas6 was not predictive of the completeness of recovery. Plasma and CSF concentrations were not related (R2=0.0003), and neither were predictive of relapse rate or EDSS progression after first relapse. Conclusions. CSF concentration of Gas6 is inversely correlated with the severity of relapse in RR-MS patients but does not predict the subsequent course of the disease.